Photovoltaic/photo-electrocatalysis integration for green hydrogen: A review. (1st June 2022) - Chatterjee, Piyali; Ambati, Mounika Sai Krishna; Chakraborty, Amit K.; Chakrabortty, Sabyasachi; Biring, Sajal; Ramakrishna, Seeram; Wong, Terence Kin Shun; Kumar, Avishek; Lawaniya, Raghavendra; Dalapati, Goutam Kumar
Graphical abstract: Highlights: Introduction to basic photovoltaic and water splitting technologies with nomenclature. Challenges and relative advantages of integrated PV-PEC over PV-EC for cost effective clean H2 . Current status of designs and material choices for affordable and scalable devices. Special emphasis on earth abundant multi-functional metal oxides such as copper oxides. Abstract: The Sun is an inexhaustible source of renewable energy, although under-utilized due to its intermittent nature. Hydrogen fuel is another clean, storable, and renewable energy as it can be readily produced by electrolysis of water, a naturally abundant resource. However, the necessary voltage for water electrolysis (>1.23 V) is high for the process to be cost effective, and therefore requires photoelectrocatalytic (PEC) cells for lowering the voltage. Powering the PEC cells with solar driven photovoltaic (PV) devices offers an all-clean efficient technology purely relying on renewable sources and therefore warrants large research attention. This review aims to provide an up to date account of the PV-PEC integrated technology for green hydrogen. We begin with the fundamentals of PV and water splitting technologies (electrolysis, photocatalysis, electrocatalysis (EC), photoelectrocatalysis (PEC)), as well as why and how the unassisted solar water splitting technology gradually progressed from PV with external electrolysers (PV-EC) to integration of PV with EC (IPV-EC) and PEC (PV-PEC). We then discuss the major challenges in PV-PEC integration and outline the major breakthroughs in design and materials development for high Solar to Hydrogen (STH) efficiency and long device lifetime. The importance of material selection and metal-oxide semiconductor nanostructures for PV-PEC integration are also discussed with a special focus on Cu-oxide as an emerging material. An outlook toward commercialization including the major guiding factors and related technologies (for e.g., PV-Thermal integration) that can maximize solar energy utilization to reduce payback time has been discussed.